Health Care Professionals' Interest in Vaccination Training in Switzerland: A Quantitative Survey - Pia Lucas Ramanathan; Pia Lucas Ramanathan; Pia Lucas Ramanathan; Nadja Baldesberger; Nadja Baldesberger; Nadja Baldesberger; Léna G. Dietrich; Léna G. Dietrich; Camilla Speranza; Alyssa Lüthy; Alyssa Lüthy; Andrea Buhl; et al. (Frontiers Media S.A., 2022)
Objectives: Health care professionals (HCPs) play an important role for patients' vaccination decisions. To counsel patients/clients appropriately, HCPs need current factual knowledge about vaccines and strong communication skills.Methods: We conducted an online survey with physicians, pharmacists, nurses, and midwives in Switzerland (01.11.2020-31.03.2021). We evaluated: 1) interest in vaccination knowledge and counseling training; 2) vaccination recommendation practices; 3) experience with vaccination counseling/administration; 4) comfort level in addressing vaccine hesitancy (VH); 5) perspectives on patient/client VH, delays, and refusals.Results: In total, 1,933 practicing HCPs responded (496 physicians, 226 pharmacists, 607 nurses, 604 midwives). 43% physicians, 31% pharmacists, 15% nurses, and 23% midwives felt comfortable counseling VH patients/clients. 96% physicians, 98% pharmacists, 85% nurses, and 91% midwives were interested in additional vaccination-related training. All professionals mentioned safety, efficacy, and side effects as topics of most interest for additional training.Conclusion: Results demonstrate a high interest among HCPs for additional vaccination-related training. In addition to factual information about vaccination, such training will likely benefit from a communication component, given the low rates of comfort reported by HCPs when counseling VH patients/clients.